Interfacial Self‐Assembly of Colloidal Nanoparticles in Dual‐Droplet Inkjet Printing. Issue 10 (24th March 2018) - Al‐Milaji, Karam Nashwan; Secondo, Ray Richard; Ng, Tse Nga; Kinsey, Nathaniel; Zhao, Hong
Abstract: The well‐known coffee‐ring effect causes colloidal particles to convectively transport toward the contact line of an inkjet droplet leading to a nonuniform deposition of the colloidal particles. In this work, the self‐assembly of colloidal particles in a dual‐droplet inkjet printing configuration to produce a nearly monolayer closely packed deposition of colloidal particles that exhibits a colorful reflection are demonstrated. By controlling the ink surface tensions and jetting parameters, the wetting droplets (the second droplet) containing colloidal polystyrene (PS) nanoparticles quickly spread over the supporting droplets (the first droplet) upon impact. The well‐ordered deposition is achieved by tuning the solvent composition of the wetting droplets and functionalization of the PS nanoparticles to encourage a network formation among the colloidal particles at the air–droplet interface. The underlying self‐assembly mechanism is insensitive to substrates and can be applied to many other material/substrate combinations. Finally, the origin of the color generation is highlighted, and the potential of the dual‐droplet inkjet printing process is discussed for fabrication of optical devices. Abstract : A nearly monolayer, closely packed deposition of colloidal nanoparticles is obtained through a dual‐droplet inkjet printing process. The well‐ordered deposition is achieved by tuning the solvent composition and functionalization of the nanoparticles to encourage a network formation among the colloidal particles at the air–droplet interface. Depending on the nanoparticle size, the deposition exhibits various structural colors due to the self‐assembled structures.